Acid-Sensing Ion Channel-1a in Articular Chondrocytes and Synovial Fibroblasts: A Novel Therapeutic Target for Rheumatoid Arthritis - Xu, Yayun; Chen, Feihu (Frontiers in Immunology, 2021)
Acid-sensing ion channel 1a (ASIC1a) is a member of the extracellular H+-activated cation channel family. Emerging evidence has suggested that ASIC1a plays a crucial role in the pathogenesis of rheumatoid arthritis (RA). Specifically, ASIC1a could promote inflammation, synovial hyperplasia, articular cartilage, and bone destruction; these lead to the progression of RA, a chronic autoimmune disease characterized by chronic synovial inflammation and extra-articular lesions. In this review, we provided a brief overview of the molecular properties of ASIC1a, including the basic biological characteristics, tissue and cell distribution, channel blocker, and factors inﬂuencing the expression and function, and focused on the potential therapeutic targets of ASIC1a in RA and possible mechanisms of blocking ASIC1a to improve RA symptoms, such as regulation of apoptosis, autophagy, pyroptosis, and necroptosis of articular cartilage, and synovial inflammation and invasion of fibroblast-like cells in synovial tissue.